Penguatan Kerukunan antar Umat Beragama Pasca Konflik di Tanjungbalai Sumatera Utara - Nasution, Abdul Gani Jamora; Bayu, Silvana; Handayani, Risma; Silalahi, Tia Anggraini; Ramadhani, Tivany; Fadilah, Fadilah (YASIN, 2022)
The Unitary State of the Republic of Indonesia (NKRI) has various ethnicities, races, and religions. Likewise the diversity that exists in the city of Tanjungbalai, the people of Tanjungbalai have a population of 108,202 people, and in Asahan Regency a population of 884,594 people. They live side by side with various other ethnic groups, such as the Toba Batak, Mandailing, Minangkabau, and Javanese. The majority of the population of the city of Tanjungbalai adhere to Islam, up to 84.67 people, the rest adhere to Protestant Christianity, Buddhism and Catholicism. But behind that, there were many disparities between religions that ended in riots. This study uses a descriptive qualitative approach. The qualitative research method is a research method that places more emphasis on aspects of understanding in depth on a problem rather than looking at problems for generalization research. In strengthening inter-religious harmony in Tanjungbalai, there have been several steps taken by both the government and religious leaders, both Islamic and Chinese leaders. This step also aims to make the people of Tanjungbalai a harmonious and more peaceful society in carrying out their daily lives.